Ethics, Religion, and Spiritual Health Intersections With Artificial Intelligence or Other Human Enhancement Technologies - Trothen, Tracy J.; Mercer, Calvin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
What does human enhancement technology (HET) and artificial intelligence (AI) have to do with religion? This book explores, specifically, the intersection of HET and AI with spiritual health, Christianity, and ethics. The exploration strengthens an emergent, robust body of publications about human enhancement ethics. What does it mean to make us "better" must also address the potential spiritual implications. Concern for spiritual health promises to make the study of religion and human enhancement ethics increasingly pressing in the public sphere. Some of the most significant possible and probable spiritual impacts of HET and AI are probed. Topics include warfare, robots, chatbots, moral bioenhancement, spiritual psychotherapy, superintelligence, ecology, fasting, and psychedelics. Two sections comprise this book: one addresses spirituality in relation to HETs and AI, and one addresses Christianity in relation to HETs and AI.